THE IN SERVICE TRAINING IN IMPROVING TEACHERS PERFORMANCE IN LEARNING PROCESS - Yetti Ellyana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The in-service training program is a training or coaching effort that gives an opportunity for someone who gets a certain job assignment, in that case, is a teacher, to get performance development. This research is a school action research (PTS). This research was conducted SDN 006 Kelawat District of Sei Lala in the academic year 2017/2018. Research data collection is done by obtaining an assessment of teacher performance in the learning process seen from indicators (a) Preparation of Actions, (b) Implementation of Actions, (c) Monitoring and Evaluation, (d) Reflection. Indicators of success achieved by researchers in this study are if the percentage of average success of all class teachers > 85. Based on the results of the study found that there was a significant increase from cycle I to cycle II. This can be seen from the overall average rating in cycle I 69.75 increasing to cycle II to 86.62. Then the learning planning indicators increased from 65.71 to 85.7. On the value of the implementation of learning the teacher's value from 70 increased to 88.57. The value in assessing student achievement increased from 74.29 to 82.14. Likewise in the aspect of carrying out the follow-up of research results from 67.86 to 90. Based on these improvements it is known that the in-service training method can improve teacher performance in SDN 006 Kelawat District of Sei Lala.